Feedback Learning Benefits and Issues in Education - Abdullah, Rahman (Archives of Business Research, 2020)
Feedback learning poses many benefits to the education system, however, in executing feedback learning in order to gain better assessment and learning processes both for the students and lecturers, the challenges are big and daunting for many universities. This paper discusses the benefits and issues in Feedback Learning related to the learning processes and assessment measures.